DNA repair genes in prostate cancer : the characterization of novel molecular mechanisms - Junila, Ylva (My University, 2020)
Prostate cancer is one of the major causes of cancer-related deaths in males in Western countries. Androgen deprivation therapy is a standard treatment for metastatic prostate cancer, aiming to suppress androgen receptor transcriptional activity. However, the prognosis for patients developing castration-resistant prostate cancer (CRPC) is poor. In CRPC, androgen receptor may stay active and stimulate the growth of the cancer despite castrate levels of androgens (e.g. dihydrotestosterone). Although therapeutic options have improved over the last years, further understanding of the mechanisms behind CRPC is needed to find novel therapeutic possibilities. In patients with metastatic CRPC, many of deleterious germline and/or somatic mutations target Breast cancer type 2 susceptibility gene (BRCA2). In this thesis, the aims were to i) study the putative crosstalk between androgen receptor signaling pathway and BRCA2, and ii) characterize one novel protein-protein interaction candidate of BRCA2 identified by a previously made mass spectrometry screen in prostate cancer cells. Commercially available human prostate cancer cell lines (PC3, LNCaP and VCaP) were used. The results indicate that after castrate conditions, dihydrotestosterone treatment regulates BRCA2 expression and localization. In addition, the expression of the putative protein-protein interactor of BRCA2 is regulated by the androgen signaling pathway. To map the site of the interaction, immunoprecipitation experiments with deletion constructs representing different parts of BRCA2 were carried out, using RAD51 and PALB2 as positive controls. In conclusion, the results suggest that the androgen signaling pathway regulates BRCA2 and its putative novel interactor.
Keywords: castration-resistant prostate cancer, DNA repair, BRCA2, androgen signaling pathway